The effect of utilizing palm oil brown sugar and red chili extract (Capsicum annuum L.) in the production of sweet and spicy palm kernel meal sauce - Hotnida Sinaga; Mimi Nurminah; Olivia Abira Rajagukguk (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Palm kernel meal is a by-product of palm oil processing that is abundant and has not been optimally utilized. This study aimed to investigate the impact of incorporating palm oil brown sugar and red chilies in the production of palm kernel meal (PKM) sauce for improving desirable physical, chemical, and organoleptic qualities. This research began with palm kernel meal fermentation to optimize the quality of palm kernel meal. Then, koji and moromi were fermented and followed by the cooking of palm kernel meal sauce. This study employed a completely randomized factorial design, with two factors: palm oil brown sugar concentration (60%, 75%, and 95%) and red chili concentration (0%, 10%, 20%, and 30%). The results showed that the interaction between palm oil brown sugar concentrations and red chili extract concentrations had a significant different effect (P<0.01) on ÂºHue, a*, b*, total soluble solids (TSS), protein, vitamin C, sensory attributes (i.e., aroma, taste, viscosity). While non-significant (P>0.05) effects were found on the value of L color, pH, reducing sugars, color, and general acceptance of palm kernel meal sauce.